Rodents - Mulungu, Loth S. (IntechOpen, 2021)
This edited volume presents a comprehensive overview of recent developments in the field of rodent behaviour, control, and management. The book contains contributions from various researchers and is edited by an expert active in the areas of pest management and ecology research. Chapters cover such topics as nutrition, nesting, and biological and physical properties of rodents.